2022
DOI: 10.1111/lapo.12181
|View full text |Cite
|
Sign up to set email alerts
|

The subtle effects of implicit bias instructions

Abstract: Judges are increasingly using "implicit bias" instructions in jury trials in an effort to reduce the influence of jurors' biases on judgment. In this article, we report on findings from a large-scale mock jury study that tests the impact of implicit bias instructions on judgment in a case where defendant race was varied (Black or White). Using an experimental design, we collected and analyzed quantitative and qualitative data at the individual and group levels obtained from 120 small groups who viewed a simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Understanding and managing these implicit biases could certainly help juries to be impartial. This need noted in our research is also confirmed in studies by Lynch et al (2022) and Zenker et al (2016) regarding the importance of facilitating judges in monitoring their own cognitive processes. For example, there are many studies on "debiasing techniques" in the literature.…”
Section: Future Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Understanding and managing these implicit biases could certainly help juries to be impartial. This need noted in our research is also confirmed in studies by Lynch et al (2022) and Zenker et al (2016) regarding the importance of facilitating judges in monitoring their own cognitive processes. For example, there are many studies on "debiasing techniques" in the literature.…”
Section: Future Implicationssupporting
confidence: 90%
“…This research examines the connection between the self-confidence expressed by the witness and the assessment of the witness' credibility Gojkovich et al (2019) Empirical study; quantitative study This study examines the effects of dress and speech style of a cowitness had on the credibility of that witness and the amount of misinformation that was accepted from the witness Kaminski and Sporer (2018) Empirical study; quantitative study This study investigated persuasive effects of behaviour cues on observer judgements of eyewitness identification decisions Klettke et al (2016) Empirical study; quantitative study This study was examined whether perceptions of credibility of female victims of sexual abuse varied across generation Y, generation X, "baby boomers" and "builders" Kwong See et al (2001) Empirical study; quantitative study This study was assessed indirectly the effect of age stereotyping on believability using a variant of Loftus' misinformation paradigm Lynch et al (2022) Empirical study; quantitative study In this article, the authors report on findings from a large-scale mock jury study that tests the impact of implicit bias instructions on judgement in a case where defendant race was varied (Black or White) Empirical study; quantitative study In this study, the authors explore the use of verbal and non-verbal modalities to build a multimodal deception detection system that aims to discriminate between truthful and deceptive statements provided by defendants and witnesses Slovenko (1999) Qualitative study and its presence and frequency can influence the credibility evaluation. In particular, it has been noted that the appropriate and pertinent use of smiling can generate a greater perception of pleasantness, safety and credibility, with a significant impact on the efficacy of the provided deposition; specifically, women who smiled were deemed more pleasant than women who did not (Nagle, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, most of the theoretical processes at play discussed thus far are unconscious or implicit in nature. Several attempts at providing jurors with instructions regarding implicit bias have been undertaken with little effect at best, or at worst, with unintended negative repercussions (Lynch et al, 2022). Ultimately, the results of our study do not preclude us from hope that jury education could help combat some of the memory issues and biases highlighted in the literature, but it does lend us to believe the best option still remains to require jurors to review all case evidence during deliberation (see Pritchard & Keenan, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, only two published studies attempted to evaluate implicit bias jury instructions (Elek & Agor, 2014;Lynch et al, 2022). However, neither were able to test the instructions' effectiveness because mock jurors did not display any racial bias.…”
Section: Unconscious Bias Juror (Ubj) Video and Instructionsmentioning
confidence: 99%